2021
DOI: 10.2147/dddt.s344052
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Endocytosis and Degradation of Antibody-Drug Conjugate T-DM1 in HER2 Positive Cancer Cells

Abstract: Purpose T-DM1 is an antibody–drug conjugate (ADC) consisting of trastuzumab and DM1 linked together. T-DM1 binds to human epidermal growth factor receptor-2 (HER2) in tumors and then triggers the endocytosis of T-DM1 and release of payload. Therefore, endocytosis efficacy is considered as a critical step for the initiation of T-DM1 therapy; however, the endocytosis mechanism of T-DM1 remains poorly understood. Meanwhile, HER2 is regarded as an internalization-resistant receptor, which hinders the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…A favorable example of a target that is significantly overexpressed in tumor tissues relative to normal tissues is the HER2/neu antigen that is expressed at lower levels on a subset of normal cells, but expressed at hundreds of thousands to over a million copies on HER2+ cancer cells. 5 Indeed, ADCs targeting the HER2 antigen have demonstrated robust internalization into HER2-targeted tumor cells with efficient payload delivery 6 , 7 that has translated to clinical benefit and ultimate drug approval. 8 , 9 In contrast, ADCs targeting tumor antigens with heterogeneous/low target antigen expression, such as the prolactin receptor with antigen densities of thousands to tens of thousands of molecules/cell, 10 failed to demonstrate clinical responses at the biologic doses tested and were subsequently terminated from future clinical development.…”
Section: Adcs As a New Class Of Targeted Therapeuticsmentioning
confidence: 99%
“…A favorable example of a target that is significantly overexpressed in tumor tissues relative to normal tissues is the HER2/neu antigen that is expressed at lower levels on a subset of normal cells, but expressed at hundreds of thousands to over a million copies on HER2+ cancer cells. 5 Indeed, ADCs targeting the HER2 antigen have demonstrated robust internalization into HER2-targeted tumor cells with efficient payload delivery 6 , 7 that has translated to clinical benefit and ultimate drug approval. 8 , 9 In contrast, ADCs targeting tumor antigens with heterogeneous/low target antigen expression, such as the prolactin receptor with antigen densities of thousands to tens of thousands of molecules/cell, 10 failed to demonstrate clinical responses at the biologic doses tested and were subsequently terminated from future clinical development.…”
Section: Adcs As a New Class Of Targeted Therapeuticsmentioning
confidence: 99%
“…MD results indicated that ricin A of CPs 2, 5, 7, 8, and 10 may most likely retain its inhibitory activity. Using molecular docking, we aimed to examine whether the selected CPs were capable of binding to trastuzumab-binding pocket on ErbB-2 since this region internalizes trastuzumab upon its binding (Austin et al, 2004) in a Caveolae/Lipid-Raft Mediated mechanism (Liang et al, 2021). The last frame of each MD trajectory entered the docking step.…”
Section: Docking Analysismentioning
confidence: 99%
“…143,144 HER2 has been linked to the activation of both clathrin-mediated and caveolae-mediated endocytosis uptakes. [145][146][147] Hence why it has been a popular anti-cancer target as these endocytosis pathways are common in most cancer cells.…”
Section: Hyaluronic Acid Receptor (Cd44)mentioning
confidence: 99%